The tale of two Ions Na+ and Cl−: unraveling onion plant responses to varying salt treatments - M. L. Romo-Pérez; C. H. Weinert; B. Egert; S. E. Kulling; C. Zörb (BMC Plant Biology)
Abstract Background Exploring the adaptive responses of onions (Allium cepa L.) to salinity reveals a critical challenge for this salt-sensitive crop. While previous studies have concentrated on the effects of sodium (Na+), this research highlights the substantial yet less-explored impact of chloride (Cl−) accumulation. Two onion varieties were subjected to treatments with different sodium and chloride containing salts to observe early metabolic responses without causing toxicity. Results The initial effects of salinity on onions showed increased concentrations of both ions, with Cl− having a more pronounced impact on metabolic profiles than Na+. Onions initially adapt to salinity by first altering their organic acid concentrations, which are critical for essential functions such as energy production and stress response. The landrace Birnförmige exhibited more effective regulation of its Na+/K+ balance and a milder response to Cl− compared to the hybrid Hytech. Metabolic alterations were analyzed using advanced techniques, revealing specific responses in leaves and bulbs to Cl− accumulation, with significant changes observed in organic acids involved in the TCA cycle, such as fumaric acid, and succinic acid, in both varieties. Additionally, there was a variety-specific increase in ethanolamine in Birnförmige and lysine in Hytech in response to Cl− accumulation. Conclusion This comprehensive study offers new insights into onion ion regulation and stress adaptation during the initial stages of salinity exposure, emphasizing the importance of considering both Na+ and Cl− when assessing plant responses to salinity.